Character and Adab Education in Indonesia, Turkey, and Japan: A Comparative Study - Syamsul Huda; Nilawati Tadjuddin; Ahmad Sholihuddin; Hisanori Kato; Korhan Cengiz (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2023)
Today's education standards have changed due to science and technology advancements. Technological developments such as the internet caused students' character development in the Industrial Revolution 4.0 to be remarkably different from the earlier generation. This study was conducted to analyze the factors of successful learning based on Auguste Comte's Law which focuses on character and adab education. This study involved comparing the education systems of three countries, Indonesia, Turkey, and Japan, to ensure successful socialization in the education system of the millennial generation. Data were collected through the observational method applied using questionnaires, interviews, and documentation from Indonesian, Japanese, and Turkey schools. This was followed by applying an analytical approach using Structural Equation Modeling (SEM) on the data obtained from the integration of questionnaire data processing and literature review. So that the method used in this study can be said to be a mixed method. Based on the study's results, obtained information and the suitability of the character education system between Indonesia, Japan, and Turkey. Character education that all parties observe, such as teachers, parents, and even school principals, can improve students' attitudes and good behavior and correlates with learning success in the Industrial Revolution Era 4.0. The success factor of character education based on the integration of schools from Japan, Turkey, and Indonesia (Pesantren Tebuireng) was found to be